2012
DOI: 10.1177/0093854811430476
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Therapeutic Climate of Prisons

Abstract: This study examined perceptions of the prison social climate in two Australian prisons from the perspective of both prison staff and prisoners. Ratings of social climate were compared between a specialist treatment prison that provides intensive rehabilitation programs to violent, sexual, and substance-using offenders and a mainstream prison that does not specialize in offender rehabilitation. The results suggested that staff and prisoners at the specialist treatment prison rated the social climate as more con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
71
2
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(79 citation statements)
references
References 46 publications
3
71
2
3
Order By: Relevance
“…The overall findings of this study slightly differ from certain literature that indicates the social climate perceptions of staff and patients are often dissimilar [24,32,[47][48][49]. Research has commonly found that staff tends to view the social climate as more positive than the patients do [23,32].…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…The overall findings of this study slightly differ from certain literature that indicates the social climate perceptions of staff and patients are often dissimilar [24,32,[47][48][49]. Research has commonly found that staff tends to view the social climate as more positive than the patients do [23,32].…”
Section: Discussioncontrasting
confidence: 99%
“…This study aligns with previous research in assessing and comparing staff perceptions of social climate are compared with juvenile perceptions in an effort to gain a consistent representation of their relationship [32,47,53]. However, several of the findings slightly differ from other literature that indicates the social climate perceptions of staff and patients are often dissimilar [24,32,[47][48][49][50]. Only one hypothesis (Hypothesis 4) in this study affirmed dissimilarity in perception.…”
Section: Discussionsupporting
confidence: 83%
“…Para la autora inglesa "el modelo de Moos está limitado" (LIEBLING y ARNOLD, 2004: 88) pues se centra en la predicción del comportamiento de los internos y deja de lado la percepción del personal sobre su entorno de trabajo. Otras críticas hacen referencia a lo obsoleto de sus términos, a su longitud que implica una gran duración en su aplicación, y su ineficacia debido a que, estadísticamente, tiene una baja consistencia interna (LIEBLING y ARNOLD, 2004: ROSS et al 2008DAY et al, 2012; CASEY, DAY y REYLONDS, 2016; WILLIAMNS et al, 2019). Para SAYLOR (1984) la influencia de la herramienta de MOOS en la investigación del clima social de prisión puede deberse más que a su "idoneidad a la escasez de otros instrumentos que midan el clima social de prisión" (LIEBLING y ARNOLD, 2004: 91).…”
Section: Del Estudio Del Clima Social Al Concepto De Calidad De Vida unclassified
“…The quantitative studies took place in a variety of therapeutic and rehabilitative focussed establishments. These included establishments focussed on the needs of violent offenders (Casey, Day, & Reynolds, 2016;Day, Casey, Vess, & Huisy, 2012) sexual and violent offenders (Woessner & Schwedler, 2014) and offenders with substance abuse treatment needs (Kubiak, 2009). The mixed method study took place in an establishment focussed on the treatment of sexual offenders (Blagden, Winder, & Hames, 2016).…”
Section: Contextual Informationmentioning
confidence: 99%